Stem Cells-based and Molecular-based Approaches in Regenerative Dentistry: A Topical Review - Tatullo, Marco; Codispoti, Bruna; Sied, Jamal; Makeeva, Irina; Paduano, Francesco; Marrelli, Massimo; Spagnuolo, Gianrico (Current Stem Cell Research & Therapy, 2019)
Background: Regenerative medicine is a growing branch of medicine aimed to treat damaged or lost tissues, to promote tissue formation and to restore both aesthetics and function. In the last years, several scientific articles have been focused on the regenerative procedures aimed to increase the survival rate of compromised teeth; the most effective approaches have been based on molecularbased and on cellular-based protocols; however, to date, both these techniques have not been carefully analysed and discussed, to know in details the advantages of each of them. Methods: A literature search was undertaken on three electronic scientific databases: Medline via PubMed, EMBASE and Google Scholar. Authors aimed to select such articles published in the time span from January 1961 until December 2017. The authors screened the titles and the abstracts including the following keywords combinations: “Pulp AND Therapy”, “Regenerative AND Endodontic”, and “Endodontics AND Tissue engineering”. After the exclusion of any not related articles, the full text of such papers related to the topics was included in this review. Results: Following the removal of duplicate articles and of other types of publications (such as erratum and corrigendum), 621 articles were selected to be included and analysed in our topical review. The articles were analysed into the following sections: cellular-based approaches for dental regeneration, molecular-based and combined cellular/molecular-based approaches for dental regeneration, and translational applications of regenerative dentistry. Conclusion: This topical review has been focused on the main, the most promising and the most innovative strategies for achieving the regeneration of dental pulp or dental tissues. The main and surprising “take-home message” is related to the great interest towards the dental-derived stem cells, characterized by a high angiogenic and neurogenic commitment. Future challenges will be focused on the development of biological-friendly regenerative strategies: the new approaches should overcome the current biological limitations, to promote the combined cellular and molecular-based treatments, able to ensure predictable clinical evidence, with the achievement of the regeneration/repairing of the compromised dental pulp and of the entire tooth structure.
Keywords: Regenerative dentistry